Edukasi Pemasangan Sarana Air Minum Di Wilayah Desa Kemambang Kecamatan Banyubiru Kabupaten Semarang - Haji, Son; Purnijanto, Bambang; Kusrin; Kustirini, Anik; Widiatmoko, Kukuh Wisnuaji (Faculty of Engineering, Universitas Semarang, 2026)
This community service program was implemented to address the limited technical knowledge and skills of residents in Kemambang Village regarding the provision of safe drinking water, while also strengthening local water management institutions. The activities were conducted using a participatory approach that combined the ABCD method, demonstrations, practices, and the application of appropriate technology. Evaluation results show an increase in community knowledge from a score of 3.13 to 4.60, and an improvement in technical skills from 2.68 to 4.40 after the training. The establishment of the Village Water Management Group (KPAD) indicates growing social capacity and collective commitment toward sustainable water management. The program also generated economic benefits through the adoption of simple, low-cost filtration systems that reduced household expenses. Overall, the program successfully enhanced community capacity in managing safe drinking water and supported village self-reliance in water service provision.